Perceived research usefulness among academic librarians: an analysis of gender - Abdullah, Salmah; Amran, Fatimah Zahrah; Ibrahim, Morni Yati (2012)
Accreditation bodies require that academic institutions engage in evidence-based decision making. Thus, it has become more important for libraries to study their own operations in a systematic and reliable manner. Many academic librarians work at institutions where librarians are required to conduct research to solve problems at work or in decision making. Some institutions take into consideration doing research as part for promotion and/or tenure. This study is done to identify and measure the level of the Malaysian academic librarians' perceptions towards research usefulness. The study also intends to investigate to whether any differences emerged between male and female librarians towards perceived research usefulness. Questionnaire was used as the research instrument involving 181 librarians from ten public higher institution libraries. Data analyses were done using SPSS version 18. The findings suggest several paths for future research about academic librarians and their research agendas.